IMPLEMENTATION ENVIRONMENTALLY SAFE WASTEWATER AS AN ELEMENT OF SUSTAINABLE HUMAN SETTLEMENTS DEVELOPMENT UKRAINE: Array - and and (Municipal economy of cities. Series: «Economy science», 2018)
The article presents the results of the analysis of the conditions of functioning of four existing methods of sewage drainage and the main provisions of the concept of sustainable development. The results of the study of the main provisions of the concept of sustainable development and the requirements of the EU on ensuring the ecological safety of drainage systems in settlements are presented. The recommendations of the international summits on sustainable development are defined. International cooperation, including city-to-city cooperation, is both necessary and mutually beneficial in promoting sustainable human settlements development. Depending on the context and the needs of the cities in each country, special attention should be paid to the most critical issues, such as changing production and consumption patterns; sustainable resource and land-use management; water supply, sanitation; environmental protection; industry; infrastructure; and basic services. The method of choice of the best technologies of ecologically safe drainage in settlements located on eutrophied water objects as an important component of ecological and social safety of settlements of Ukraine is offered. The relative importance of certain factors for the introduction of environmentally safe water disposal using the analytic hierarchy process (HР) is defined as the basis for the management system of ecologically safe water using - an important component of environmental and social security of Ukrainian settlements. The Analytic Hierarchy Process (AHP), introduced by Thomas Saaty (1980), is an effective tool for dealing with complex decision making, and may aid the decision maker to set priorities and make the best decision. By reducing complex decisions to a series of pairwise comparisons, and then synthesizing the results, the AHP helps to capture both subjective and objective aspects of a decision. Keywords: sustainable development, ecologically safe water using, environmental safety, analytic hierarchy process